Uneven Effects of Sleep Apnea on Semicircular Canals and Otolithic Organs - Xu, Xin-Da; Chen, Bin-Jun; Sun, An-Rong; Zhang, Qing; Cheng, Ying; Ren, Dong-Dong; Yu, Jing; Luo, Hui-Ping (Frontiers in Neurology, 2022)
OBJECTIVE: This study aimed to explore how obstructive sleep apnea (OSA) affects the function of each vestibular organ and to identify the correlations among them. METHODS: A prospective study was conducted involving 32 healthy controls and 64 OSA patients. The objective detection methods of the utricle and saccule are vestibular-evoked myogenic potentials (VEMPs). A combination of the caloric test and video head impulse test (vHIT) was used to comprehensively evaluate the objective function of semicircular canals. RESULTS: Elevated thresholds (p<0.001), decreased waveform amplitudes (p<0.001), prolonged first wave latencies (p<0.001) and shortened first interpeak latencies (p<0.001) were observed in both ocular VEMP (oVEMP) and cervical VEMP (cVEMP). A significant difference was found in the caloric test comparison (chi²=4.030, p=0.045) but not in the vHIT. The intergroup comparison of normal rates among the VEMPs, caloric test, and vHIT groups showed significantly different (p<0.001). CONCLUSIONS: The impairment of vestibular function in OSA patients was uneven and biased. More attention should be given to vestibular dysfunction in the diagnosis and treatment of OSA.